Load shedding strategies to mitigate fault induced delayed voltage recovery: trends and development (Publicaciones en Ciencias y Tecnología, 2022)
Fault-induced delayed voltage recovery (FIDVR) is a major threat to the voltage stability of electrical power systems with load dominated by induction motors. Over the past decade, load rejection strategies have been proposed to mitigate FIDVR and avoid voltage instability. This paper analyzes the load shedding strategies published in the scientific literature to mitigate FIDVR. A classification of scientific publications based on a systematic method of evaluation of characteristics is applied, for which the characteristics of the strategies are identified according to their methodological and technological aspects of design and functionality; further the characteristics are evaluated according to their degree of belonging and with this the analyzed publications are classified. The result of the analysis of the load shedding strategies, based on empirical rules and analytical methods, revealed that they are not yet fully efficient in determining the minimum amount of load to be disconnected, nor fast enough to effectively reduce the voltage recovery time; and it is also found that design methods based on artificial intelligence represent a great opportunity to overcome these challenges.
Keywords: fault-induced delayed voltage recovery; load shedding; short term voltage instability; induction motors